If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 5) = (6x + 10) Reorder the terms: (5 + 2x) = (6x + 10) Remove parenthesis around (5 + 2x) 5 + 2x = (6x + 10) Reorder the terms: 5 + 2x = (10 + 6x) Remove parenthesis around (10 + 6x) 5 + 2x = 10 + 6x Solving 5 + 2x = 10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5 + 2x + -6x = 10 + 6x + -6x Combine like terms: 2x + -6x = -4x 5 + -4x = 10 + 6x + -6x Combine like terms: 6x + -6x = 0 5 + -4x = 10 + 0 5 + -4x = 10 Add '-5' to each side of the equation. 5 + -5 + -4x = 10 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 10 + -5 -4x = 10 + -5 Combine like terms: 10 + -5 = 5 -4x = 5 Divide each side by '-4'. x = -1.25 Simplifying x = -1.25
| 6x^3=-22x+28x^2 | | -21.263+n=-44.464 | | Y-6=43 | | 6y-22=20 | | Logx=-3/2 | | 4f-8=16 | | 1=(0.02*.02)+2*(0.02x)+(x*x) | | 1=ax+bx+a | | 1=(0.02*.02)+(0.02x)+(x*x) | | 2(5-x)=x+1 | | 35-y=270 | | X^2+4x-236=0 | | solve-8b+9+6b=-3b+14 | | C^2-8c=4 | | 5(4x-2)+x=3(x+10)-10 | | 10x^2+3x+7=8 | | 0.5x*0.2x=0.1875 | | -25.70-v=-40.3 | | y=-4x+23 | | y^2-6y=x-5 | | ((5x^-3)/(-3)) | | 5x^-3/-3 | | 0=18x | | 3x-5x^2=-4 | | 0.5x*0.2x=0.25 | | 25.39=28.89-c | | 25.39= | | .2y-5=7y-5 | | 5(2x+1.2)=(x-1.5) | | 3(2x+5)-8=2(X+24)-2x+10 | | -6.5-x=13.4 | | 4x^4-8x^2-12=0 |